Comaximal factorization in a commutative Bezout ring - Zabavsky, B.V.; Romaniv, O.; Kuznitska, B.; Hlova, T. (Algebra and Discrete Mathematics, 2020)
We study an analogue of unique factorization rings in the case of an elementary divisor domain.